Psychometric Properties of Scared-C Scale in a Romanian Community Sample and Its Future Utility for Dental Practice - Sorana-Maria Bucur; Adela Moraru; Beata Adamovits; Eugen Silviu Bud; Cristian Doru Olteanu; Luminița Ligia Vaida (MDPI AG, 2022)
The psychological management of children and adolescents in need of pedodontics or orthodontic treatments continues to be an essential objective in dental activity because along with the accuracy of the techniques that are used, anxiety reduction, and knowledge of how to approach the patient are necessary for the treatment to be successful. Therefore, our study aimed to validate the Screen for Child Anxiety Related Emotional Disorders questionnaire, the child version of 41 items (SCARED-C) in the Romanian population for later use in pediatric dentistry. The instrument showed moderate to good internal consistency (α Cronbach from 0.63 to 0.91 for the total scale) and good test-retest reliability (0.70) on a subset of a sample comprising 85 children. A confirmatory factorial analysis (CFA) was conducted to test the factor structure of the Romanian version of the SCARED-C; the results showed that SCARED-C has good psychometric properties that can be used for screening anxiety in Romanian children and adolescents. The implications of using the SCARED-C in dental practice are discussed. Future studies need to be conducted to explore the convergent and discriminative validity of the instrument and its sensitivity to current DSM-V criteria. Application on a pediatric dental sample is also required.